The Influence of Brand Loyalty, Brand Awareness, Brand Image, and Perceived Quality on Brand Equity in MS Glow - Unik Dwi Lestari; Lusi Yanah (Business Management Journal, 2023)
This study aims to determine the effect of brand loyalty, brand awareness, brand image, and perceived quality on MS Glow. The data collection technique was carried out by distributing Likert questionnaires which were distributed online on Google Forms. The sampling technique uses purposive sampling. Data were taken from 202 respondents and analyzed using SPSS 26 and SEM Lisrel 8.8. Respondents were taken from MS Glow users who lived in Tangerang Regency. Based on the test results, it was found that the variables brand loyalty, brand awareness, and perceived quality had a positive and significant influence on brand equity and brand image had no positive effect and did not support brand equity.